KEPASTIAN HUKUM KASASI PERKARA TATA USAHA NEGARA YANG DIKELUARKAN OLEH PEJABAT DAERAH - Yohanes Pattinasarany (Universitas Kristen Satya Wacana, 2022)
Cassation in state administrative cases is a legal remedy against judex factie court decisions, but not all judex factie court decisions can be appealed. There are restrictions on the cassation of state administrative cases as stipulated in Article 45A paragraph (2) Letter c of Law No. 5 of 2004 concerning Amendments to Law No. 14 of 1985 concerning the Supreme Court, that state administrative cases that are exempt from legal proceedings for cassation are state administrative cases whose object of a lawsuit is a decision issued by a regional official whose decision range is valid in the region concerned. However, there is a cassation decision on state administrative case no. 174 K/TUN/2013, the object of which is the Mayor's Decree concerning the Ratification of the Village Head, and the Cassation Decision on State Administrative Cases No. 176 K/TUN/2020, of which the object of the lawsuit is the Regent's Decree concerning the Ratification of the Head of the State Government (customary village head). The two cassation decisions belong to the category of state administrative cases, which are limited to legal cassation because the two objects of the lawsuit are the decisions of the regent and mayor, who are regional officials. The scope of the regent and mayor's decision also only applies to the area concerned and does not apply. In other places, the cassation decisions of the two cases in question do not provide legal certainty to the limitation of cassation in administrative cases. In addition, those decisions may have legal consequences that they will eliminate the implementation of cassation in State administrative cases and give rise to the right for each party to appeal even though the filing of the lawsuit is issued by a regional official and the scope of its application is only in the region.